Expositions of the Psalms - Erasmus, Desiderius, -1536 (University of Toronto Press, 1997)
Between 1515 and 1533 Erasmus wrote commentaries on eleven psalms. His principal aim was, as in his Paraphrases, to contribute, through the exposition of the Bible, to the renewal of preaching and devotional literature. This is the first of three volumes of the Expositions of the Psalms in the Collected Works of Erasmus. It contains the commentaries 'Blessed the Man' / 'Beatus vir,' 'Why Did the Nations Rage?' / 'Quare fremuerunt gentes?,' 'O Lord, How Have My Tormentors Multiplied?' / 'Domine quid multiplicati?,' and 'A Sermon on the Fourth Psalm' / 'In psalmum quartum concio.' The commentaries in this volume recall many of Erasmus' favourite preoccupations and themes: his concern with Christian ethics; his constant exhortation to readers to practise the philosophia Christi and place their trust in God; the importance of exercising, in deeds rather than merely in words, charity towards those less fortunate than oneself, and the need to avoid vanity and falsehood at every turn. Erasmus stresses the role of the psalms as a comfort in tribulation and an exhortation to piety - in the very specific meaning that he gives to that word. He remains ever concerned about how the psalms relate to each individual in the conduct of his or her life. The introduction by Dominic Baker-Smith provides an important framework for the understanding and appreciation of all three volumes of the Expositions of the Psalms.
Keywords: Bible. -- Psalms -- Commentaries -- Early works to 1800.; Bible. -- Psalms; HISTORY -- Renaissance.; Commentaries; Early works